1997
DOI: 10.1038/sj.onc.1201279
|View full text |Cite
|
Sign up to set email alerts
|

Association of PTP-PEST with the SH3 domain of p130cas; a novel mechanism of protein tyrosine phosphatase substrate recognition

Abstract: The protein tyrosine phosphatase PTP-PEST displays remarkable substrate specificity, in vitro and in vivo for p130cas a signalling intermediate implicated in mitogenic signalling, cell-adhesion induced signalling, and in transformation by a variety of oncogenes. We have identified a high affinity interaction between the SH3 domain of p130cas and a proline-rich sequence (P335PPKPPR) within the C-terminal segment of PTP-PEST. Mutation of proline 337 within this sequence to alanine significantly impairs the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
117
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 31 publications
3
117
1
1
Order By: Relevance
“…CD2BP1 also independently binds a second intracellular ligand, the tyrosine phosphatase PTP-PEST, at a site separate from CD2. Because PTP-PEST dephosphorylates p130 cas , it is probable that focal adhesion can be readily down-modulated by this means (30,53). Transfection analysis in COS cells and Jurkat cells vis-à-vis CD2-dependent adhesion function are consistent with this view (20).…”
Section: Discussionmentioning
confidence: 64%
“…CD2BP1 also independently binds a second intracellular ligand, the tyrosine phosphatase PTP-PEST, at a site separate from CD2. Because PTP-PEST dephosphorylates p130 cas , it is probable that focal adhesion can be readily down-modulated by this means (30,53). Transfection analysis in COS cells and Jurkat cells vis-à-vis CD2-dependent adhesion function are consistent with this view (20).…”
Section: Discussionmentioning
confidence: 64%
“…In a screen for substrates of tyrosine phosphatase PTP-PEST using a substratetrapping approach, Garton et al (1996) identified that p130 Cas can interact with catalytically inactive PTP-PEST (Garton et al 1996). However, it was later discovered, through a more careful mapping experiment, that the major interaction domain between p130 Cas and wild-type PTP-PEST is at the SH3 domain of p130 Cas (Garton et al 1997). Similarly, over-expression of PTP1B, another abundant intracellular tyrosine phosphatase, has been shown to interact with p130 Cas through its SH3 domain (Liu et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cas , Hef1/Cas-L, Sin/Efs, and Csk (2)(3)(4)(5). In addition, a novel and non-classical polyproline region in PTP-PEST has been implicated in the binding of paxillin and Hic-5 (6 -9).…”
mentioning
confidence: 99%
“…The identification of p130 Cas as a substrate of PTP-PEST using catalytically inactive substrate trapping mutants of the enzyme was a major step in the elucidation of some of the biological functions of this protein (3,5,12). Although the PTP domain of PTP-PEST is sufficient to recognize the p130 Cas phosphorylated on tyrosine residues in vitro, an additional level of specificity is mediated via a SH3 domain-dependent association in vivo (3,5).…”
mentioning
confidence: 99%